2015
DOI: 10.1007/s00284-015-0855-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Enumeration of Streptococcus agalactiae from Bovine Milk Samples by Real-Time Polymerase Chain Reaction

Abstract: The aim of this study was to evaluate the use of real-time polymerase chain reaction (qPCR) combined with DNA extraction directly from composite milk and bulk tank samples for detection and enumeration of Streptococcus agalactiae (SAG) causing subclinical mastitis. Dilutions of sterile reconstituted skim milk inoculated with SAG ATCC 13813 were used to establish a standard curve (cfu/mL) for the qPCR assay targeting SAG. The analytical sensitivity and repeatability of the qPCR assay were determined. Bulk tank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Being an obligate intramammary pathogen, the bovine udder is recognised as the only reasonable source of S agalactiae , and consequently, the specificity in BTM approaches 100 per cent (Keefe 2012, De Carvalho and others 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being an obligate intramammary pathogen, the bovine udder is recognised as the only reasonable source of S agalactiae , and consequently, the specificity in BTM approaches 100 per cent (Keefe 2012, De Carvalho and others 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Concerning the other major contagious mastitis pathogen, the authors found that the prevalence of S agalactiae in the present study is higher than the prevalence found in Denmark, which ranged between 3 per cent and 7 per cent (Rynasek and others 2009, Katholm and others 2012), and the 7.7 per cent prevalence found in Québec (Francoz and others 2012), but this result is similar to the 26 per cent of positive BTM samples found in Australian herds (Phuektes and others 2003). Being an obligate intramammary pathogen, the bovine udder is recognised as the only reasonable source of S agalactiae , and consequently, the specificity in BTM approaches 100 per cent (Keefe 2012, De Carvalho and others 2015).…”
Section: Discussionmentioning
confidence: 99%